Prevalence of Varroa destructor and first report of Nosema sp. in Apis mellifera drone congregation areas - Escalante, Karen Mayra Dayana (2023)
Varroosis and nosemosis are diseases that affect honey bees (Apis mellifera) and there-fore have a great impact on beekeeping worldwide. These parasites can be dispersed by drones and, in the case of Varroa destructor (etiological agent of varroosis), its presence has been reported in areas of natural fertilization of A. mellifera, known as Drone Congregation Areas (DCA). Previously, several DCAs were identified in Argentina and progress was made in their topographic and genetic characterization, and sanitary studies were also initiated. In this study, three DCA and one apiary located in the province of Tucumán were monitored for four years, and the presence of V. destructor and Nosema sp. was evaluated. The results indicated the presence of V. destructor in the drone samples of the DCA throughout the study. Although a trend of decreasing parasitization over time was observed, no statistically significant dif-ferences were found between years or among the considered DCAs. The presence of Nosema sp. was detected for the first time in the DCA, with samples exhibiting high spore load. The results support the role of drones in the dynamics and dispersal al of diseases and allow us to conclude that the analysis of DCAs represents a key tool for monitoring the health of bee populations, complementary to the analyses carried out in apiaries.